%% %% An UIT Edition example %% %% Example 10-03-1 on page 202. %% %% Copyright (C) 2010 Herbert Voss %% %% It may be distributed and/or modified under the conditions %% of the LaTeX Project Public License, either version 1.3 %% of this license or (at your option) any later version. %% %% See http://www.latex-project.org/lppl.txt for details. %% %% %% ==== % Show page(s) 1 %% \documentclass[]{exaarticle} \pagestyle{empty} \setlength\textwidth{375.57637pt} \AtBeginDocument{\setlength\parindent{0pt}} \StartShownPreambleCommands \usepackage{amsmath} \StopShownPreambleCommands \begin{document} $\begin{array}{rcll} y & = & x^{2}+bx+c\\ & = & x^{2}+2\times\dfrac{b}{2}x+c\\ & = & \underbrace{x^{2}+2\times\dfrac{b}{2}x+\left(\frac{b}{2}\right)^{2}}- {\left(\dfrac{b}{2}\right)^{2}+c}\\ & & \qquad\left(x+{\dfrac{b}{2}}\right)^{2}\\ & = & \left(x+\dfrac{b}{2}\right)^{2}-\left(\dfrac{b}{2}\right)^{2}+c & \left|+\left({\dfrac{b}{2}}\right)^{2}-c\right.\\ y+\left(\dfrac{b}{2}\right)^{2}-c & = & \left(x+ \dfrac{b}{2}\right)^{2} & \left|\strut(\textrm{vertex form})\right.\\ y-y_{S} & = & (x-x_{S})^{2}\\ S(x_{S};y_{S}) & \,\textrm{or}\, & S\left(-\dfrac{b}{2};\,\left(\dfrac{b}{2}\right)^{2}-c\right) \end{array}$ \end{document}